The Role of Colchicine in the Treatment of Autoinflammatory Diseases - Liantinioti, Georgia; Argyris, Antonios A.; Protogerou, Athanase D.; Vlachoyiannopoulos, Panayiotis (Current Pharmaceutical Design, 2018)
Colchicine has been longstanding and widely used for the treatment of acute gout flares and prevention of gout relapses. Its use has been extended to a series of autoinflammatory diseases, such as familial Mediterranean fever and more recently to periodic fever with aphthous stomatitis, pharyngitis and adenitis, Behcet's disease and idiopathic recurrent acute pericarditis. In this review, we summarize current indications of colchicine use, discuss its pharmacokinetics and mechanism of action and examine its use in the treatment of autoinflammatory diseases. Further understanding of the underlying mechanisms of the latter conditions as well as identification of the therapeutic efficacy and treatment target of colchicine may lead to more effective management of these diseases.
Keywords: pharyngitis